SAT0638 Clinical activity, ultrasound assessment and drug monitoring in rheumatoid arthritis patients receiving ANTI-TNF-α therapy with extended interval of administration. (15th June 2017) - Gallego, JM Senabre; Salazar, J Rosas Gόmez de; Mingot, M Marco; Naranjo, A; Llinares-Tello, F; Pons, A; Barber-Vallés, X; Santos-Soler, G; Salas-Heredia, E; Cano, C; Lorente, M; García, JA Gόmez; et al.
Abstract : Objectives: To assess clinical activity, ultrasound synovitis and drug levels in rheumatoid arthritis (RA) patients receiving anti-TNFα therapy with extended interval of administration (EIA). Methods: Prospective observational study. Population: RA patients, in clinical remission, receiving adalimumab (ADL) or etanercept (ETN) with EIA. Clinical activity was assessed by DAS28-ESR, DAS28-CRP, CDAI and SDAI scores at each visit. Twelve-joint ultrasound assessment (elbows, wrists, 2nd and 3rd metacarpophalangeal joints, knees and ankles) was performed evaluating synovitis through B-mode (BM) and Color Doppler signal (CD). A BM and CD score was calculated summing the highest score from each joint to a maximum of 36 points. We consider positive score >1 point. Serum drug levels were measured using Promonitor® ELISA kits (Progenika Biopharma-Grifols, Spain). Results: A total of 39 patients were included since February 2011 to December 2016. One patient was excluded due to blindness violation and 2 patients never reduced anti-TNFα due to low drug levels. 31 patients were women (82%) and the mean age was 61 (39–81) years. Most patients were RF positive (87%) and ACPA positive (74%). 22 patients were with ADL treatment and 16 with ETN. 32 patients (82%) were with DMARD concomitant treatment (18 MTX (46%), 11 LEF (18%), 2 HCQ (5%), 1 SSZ (2%)) and 7 patients were with low-dose CS (18%). Mean time from diagnosis was 14, 95 years (range 2, 15 – 52, 31) and Mean time with current biologic drug was 4, 21 years (range 1, 39 – 11, 07). Nine patients (24%) returned to standard interval due to worsening of clinical activity and one discontinued treatment due to septic arthritis. All of them returned to clinical remission and no anti-drug antibodies were detected. Clinical activity scores, ultrasound scores and drug levels are summarized in table 1 . Conclusions: 1. Clinical remission was sustained in most patients receiving ADL or ETN in extended interval of administration (EIA). 2. Drug levels decrease over time. 3. Some patients (24%) returned to standard interval of administration due to clinical worsening. 4. Some patients show subclinical ultrasound synovitis in B-mode (90%) or Color Doppler (50%) 5. It would be advisable to perform periodic ultrasound and monitoring of anti-TNFα levels to maintain clinical remission in patients with EIA. Acknowledgements: This study was supported by a research grant from Fundaciόn Española de Reumatología and AIRE-MB. Disclosure of Interest: J. Senabre Gallego Speakers bureau: MSD, Novartis, Abbvie, UCB, BMS, J. Rosas Gόmez de Salazar: None declared, M. Marco Mingot: None declared, A. Naranjo: None declared, F. Llinares-Tello: None declared, A. Pons: None declared, X. Barber-Vallés: None declared, G. Santos-Soler: None declared, E. Salas-Heredia: None declared, C. Cano: None declared, M. Lorente: None declared, J. A. García Gόmez: None declared, J. Molina: None declared